Dance for people with chronic respiratory disease: a qualitative study. Issue 10 (13th October 2020) - Philip, Keir Elmslie James; Lewis, Adam; Williams, Sian; Buttery, Sara Catherine; Polkey, Michael I; Man, William; Fancourt, Daisy; Hopkinson, Nicholas S
Abstract : Objectives: To explore the experiences and perceived impact on health and well-being related to participation in a dance group for people with chronic respiratory disease (CRD). Design: An exploratory qualitative study using thematic analysis of semistructured interviews. Setting: A community dance group in a UK health centre. Participants: Convenience sample of long-term dance group participants. Intervention: Weekly community dance sessions designed for people with breathlessness, lasting 75 min, led by a trained community dance leader. Results: Convenience sample of eight participants, six females, aged 57–87 years (mean 75), with a median 2-year attendance at weekly dance sessions. Long-term attendance was driven by strongly held beliefs regarding the health and well-being benefits of participation. Four key themes were identified: dance as (1) a holistically beneficial activity, with physical and psychosocial health benefits including improved or maintained physical fitness and psychological well-being, and reduced need for healthcare; (2) an integral part of their life; (3) an enjoyable activity; and (4) a source of deep social cohesion. Conclusions: Dance group participants perceived a broad range of health benefits of relevance to the biopsychosocial impacts of their respiratory disease. The themes identified are useful in the ongoing planning and evaluation of dance as a holistic complex intervention for people with CRD. Further research is required to assess the extent of health impacts identified, and how dance might be most effectively placed as an option in the management of CRD. Trial registration number: NCT04006015 .